Mechanochemical Synthesis of Polymorphic Urea ⋅ Adipic Acid Cocrystal as a Sustained‐Release Nitrogen Source. Issue 3 (23rd December 2021) - Parakatawella, Shalika; Gogoi, Diptajyoti; Deka, Poonam; Xu, Yizhi; Sandaruwan, Chanaka; Jayasundera, Anil C. A.; Arhangelskis, Mihails; Thakuria, Ranjit; Adassooriya, Nadeesh M.
Abstract: A 2 : 1 urea ⋅ adipic acid cocrystal was obtained in two polymorphic forms (Form I reported earlier, and Form II synthesized in this study) using mechanochemistry as well as solution crystallization. Lower solubility and leaching study showed the newly synthesized urea ⋅ adipic acid 2 : 1 cocrystal to be an efficient sustained‐release nitrogen fertilizer compared to commercially available urea. Abstract : Crystal clear : Thermodynamically more stable Urea ⋅ adipic acid 2 : 1 cocrystal Form II is synthesized using mechanochemistry. Low solubility and sustained‐release property make the newly synthesized cocrystal an excellent alternative to commercial urea as a nitrogen fertilizer for crop growth.